Anti-hyperglycaemic Effect of Methanolic Extract of Tridax Procumbens in Alloxan-Induced Diabetic Wistar Rats - Ngaski, A.A.* 1, Isah, O.S. 1 and Mainasara, A.S. 2 (Sokoto Journal of Medical Laboratory Science)
Plant based herbs have historically been a significant source of pharmaceutical molecules for the treatment of metabolic illnesses like diabetes mellitus. This research was aimed at assessing the antihyperglycaemic effect of Tridax procumbens plant on alloxan-induced diabetic wistar rats. The whole plant of T. procumbens was collected within UDUTH, Sokoto premiss, dried under shade and extracted with absolute methanol by maceration for 72 hours with an obtainable percentage yield of 6.9%. The dried mass was used for preliminary p h y t o c h e m i c a l , a c u t e t o x i c i t y a n d pharmacological analysis. Diabetic rats were treated with 250 mg/kg of metformin, 250 mg/kg and 500 mg/kg body weight of T. procumbens extract for 14 consecutive days. At the end of the experiment blood samples were collected into sample containers to assess the hypoglycaemic effect of the methanolic extract of T. procumbens plant by analyzing fasting plasma glucose and fasting lipid profile level for all experimental animals and compared with diabetic control. The pancreas for all groups were harvested for histological examination . Preliminary phytochemical analysis of methanolic extract of T. procumbens indicated the presence of alkaloid, steroids, flavonoids, tannins and saponin compounds and the LD50 was greater than 5000mg/kg. The methanolic extract of whole plant of at 250 and 500 mg/kg shows significant decrease (p<0.05) in fasting plasma glucose and some lipid profile parameter (TG, TC, LDL-C, and AI) except for (HDL-C) which significantly increased (p<0.05) when compared with diabetic control. The pancreas histology for groups treated with extract of T. procumbens at dose 250 and 500 mg/kg shows absence of islet cells. Methanolic extract of Tridax procumbens plant has a blood glucose lowering potentials against alloxan-induced diabetic wistar rat. However, chronic toxicity studies and molecular phytochemical studies should be conducted to access the pancreatic effect over time and its active components.